Concept and features of protection of rights of war veterans - Pohosian, Robert (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
This article describes the concepts and features of protecting the rights of war veterans.It is argued that protection is a part of protection, is its constituent element, but has an autonomous character along with this; secondly, protection can manifest itself in the form of civil-law, administrative-law, criminal-law protection, which have a special content and a system of specific preventive measures, at the same time, protection is characterized by the possibility of applying civil-law, administrative-law, criminal- legal coercion; thirdly, each of the mentioned types of protection and protection is responsible for its own group of public legal institutions, which are designed to carry out activities in the form of protection or protection of certain rights or their combination. The statement that it is more appropriate to use the construction "protection of the rights of war veterans" for the rights of war veterans, which includes active protection if necessary, is argued.It is noted that war veterans are persons who took part in hostilities, anti-terrorist operations and other forms of armed struggle for the defense of the Motherland or in other hostilities on the territory of other states, in accordance with international agreements, medical representatives, volunteers, war invalids, liquidators subversive-terrorist groups, UPA soldiers, peacekeepers, etc., who bear physical and psychological consequences of participating in these actions, and need special support and assistance from the state.The signs of the concept of "war veteran" are distinguished: the participation of a military person in armed conflicts, hostilities and other forms of armed struggle on the side of Ukraine or other friendly countries; confirmed participation of a military person in an armed conflict, hostilities and other forms of armed struggle, which was carried out in accordance with the requirements of the law; the fact of receiving wounds, contusions, injuries or disability as a result of participation in armed conflicts, hostilities and other forms of armed struggle (optional feature); term of service in the armed forces, police, Security Service of Ukraine, State Border Service of Ukraine and other military formations; confirmation of veteran status with relevant documents (military ID card, veteran certificate, certificate of injury or disability, etc.); need special benefits and support from the state; introduction of special registration of war veterans in accordance with legislation.